Detection of HOCl in the Antarctic stratosphere - Toon, G. C.; Farmer, C. B. (1989)
An integrated vertical column abundance of 1.5 + or - 0.4 x 10 to the 14th molec/sq cm of HOCl has been inferred from high resolution infrared solar spectra measured by the JPL MkIV interferometer from the NASA DC-8 aircraft during flights over Antarctica in September 1987. This result was obtained by averaging spectra recorded at different times, dates, and locations, but may be considered a mid-morning measurement at a solar zenith angle of 88.2 degrees from 79 deg S, 83 deg E on September 20. This result poses an important constraint on the amount of HO(x) inside the Antarctic winter vortex and on the contribution of the HOCl catalytic cycle to the observed springtime ozone depletion.